Pengaruh Kesadaran Metakognitif terhadap Motivasi Belajar dan Kaitannya dengan Hasil Belajar Matematika Siswa Kelas XI SMA Negeri di Kota Pare-Pare - Nilam Permatasari Munir (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
The study aims to analyze the descriprition of metacognitive awareness toward learning result of mathematics directly and indirectly through learning motivation of grade XI IPA student of public senior high school in Pareparecity. The study is an ex-post facto which casuality. The populations of the study were 520 grade XI IPA students of SMAN inParepare of academic years 2013/2014 with as many as 221 samples. Technique used in selecting the samples was proporsional random sampling. The instrument used for the study were (1) scale of metacognitive awareness, (2) scale of intrapersonal intelligence, (3) scale of learning motivation, (4) scale of attitude on mathematics and (5) test of mathematics learning outcomes. Data were analyzed using descriptive statistics analysis and SEM (Structural Equation Modelling) analysis. The results of the study indicate that (1) most of grade XI IPA students at SMAN in Parepare has metacognitive awareness with high category, learning motivation is in extremely high category, the learning result is in low category, (2) metacognitive awarenees directly give positif influence toward learning result of Mathematics and indirectly gives negative influence toward cognitive learning result of Mathematics through motivation learning.